2012
DOI: 10.1016/j.healthpol.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for support services among adolescents and young adults with cancer or a blood disorder: A discrete choice experiment

Abstract: Providing the types of support services that people prefer should maximise effectiveness. This study suggests that AYA patients require support services that included financial aid, assistance returning to work/study, emotional support for themselves and for their family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 36 publications
(36 reference statements)
1
36
0
Order By: Relevance
“…The full findings from the study affirmed the evidence in the literature that diagnosis and treatment for cancer, in this case hematological malignancies, can for some individuals lead to significant financial hardship, which will create a need for financial assistance (Access Economics, ; Goodall, King, Ewing, Smith, & Kenny, ; Stey, Fei, Franco, Mendelson, & Bickell, ). This article examines the specific findings that indicate a critical period for receiving financial counseling or assistance, and the evidence that during this time many patients do not know about or have the required information to access such assistance when in need.…”
Section: Resultssupporting
confidence: 70%
“…The full findings from the study affirmed the evidence in the literature that diagnosis and treatment for cancer, in this case hematological malignancies, can for some individuals lead to significant financial hardship, which will create a need for financial assistance (Access Economics, ; Goodall, King, Ewing, Smith, & Kenny, ; Stey, Fei, Franco, Mendelson, & Bickell, ). This article examines the specific findings that indicate a critical period for receiving financial counseling or assistance, and the evidence that during this time many patients do not know about or have the required information to access such assistance when in need.…”
Section: Resultssupporting
confidence: 70%
“…Twenty‐six articles met eligibility for study inclusion and addressed the social domains of interest (ie, education, employment, financial burden, interpersonal relationships, and supportive care) (Table ) . The majority of studies were cross‐sectional in design and used surveys or interviews for data collection.…”
Section: Resultsmentioning
confidence: 99%
“…The papers that elicited pediatric cancer patient perspective on their own spiritual care needs were primarily timed during the survivorship timeframe, as patients retrospectively described spirituality in the setting of survivorship . Child voice was included in the following formats: an open‐ended interview on hope, spiritual quality‐of‐life interviews, needs assessment discrete choice exercise, interview responses about coping strategies during chemotherapy hospitalizations or transplant, in association with advance care planning experience, and in integrative therapy use …”
Section: Resultsmentioning
confidence: 99%
“…The findings of studies included in this review did not universally endorse a preference for spiritual support, thus highlighting the need for spiritual needs assessment as essential to linking preferred support and available spiritual care resources. For example, one Australian study indicated that adolescent and young adult patients and their caregivers were indifferent toward spiritual support but had a clear preference for support for patient and family emotional functioning, support for financial needs, and support for return to school and work . However, the authors of that study noted the significant heterogeneity in their data, suggesting that a portion of their sample indeed valued spiritual support even though group findings were not significant.…”
Section: Discussionmentioning
confidence: 99%